KESIAPAN KEPALA SEKOLAH MENENGAH ATAS NEGERI DALAM MENGIMPLEMENTASIKAN KURIKULUM TINGKAT SATUAN PENDIDIKAN (KTSP) DI KABUPATEN TANAH DATAR - HARDIANTO -; ERISMEN SYAM (Universitas Pasir Pengaraian, 2009)
The background of this research is that there are still some of senior high school headmasters in Tanah Datar (Kab) who still don’t understand in implementing KTSP, based on their knowledge, understanding and their capability. This is a descriptive research. All of the sample were taken from all is population. This research used quistionaire and semantic differensial model to collect the data. The data were analyzed using average score formula. This research shows: 1) Senior high school headmasters are categorized quite ready in knowledge side to implement KTSP in Tanah Datar (Kab), with average score 8,21; 2) Senior high school headmasters are categirized quite ready in undestanding side to implement KTSP in Tanah Datar (Kab), with average score 7,88; 3) Senior high school headmasters are categorized quite ready in their capability to implement KTSP in Tanah Datar (Kab), with average score 8,20. Generally, senior high school are categorized quite ready to implement KTSP, with the total average score is 8,09